Review Literatur: Analisis Penyebab Pending Claim Berkas BPJS Kesehatan Pelayanan Rawat Inap di Rumah Sakit - Dhamigus, Yofen; Nurwahyuni, Atik (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2024)
Health service providers include all Health Facilities that collaborate with BPJS Health in the form of First Level Health Facilities and Advanced Level Referral Health Facilities. This is the hospital's focus so that there are no obstacles in BPJS Health claims that could affect the hospital's operational cash became disturbed. The search for sources was based on the literature review method based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). The two main data bases used in the search were Google Scholar and Pubmed. With the last search on February 17 2024. Inclusion criteria These are; (1) the article uses Indonesian or English; (2) this article was published in the last 2 years, namely 2022 to 2023; (3) quantitative and qualitative research; (4) the article is available in full manuscript form. From the search The keywords used are;